The first records on the genus Acalyptris from the Caribbean (Lepidoptera: Nepticulidae) - Stonis, Jonas R.; Remeikis, Andrius (Zootaxa, 2015)
In this paper we describe three new species of Acalyptris Meyrick (Lepidoptera: Nepticulidae): Acalyptris nigrisignum Remeikis & Stonis, sp. nov. from the Country of Curaçao (formerly the Netherlands Antilles), A. trigonijuxtus Remeikis & Stonis, sp. nov. from British Virgin Islands, and A. dominicanus Remeikis & Stonis, sp. nov. from Dominica. A pictorial key is provided for two newly established species complexes: bicornutus and tenuijuxtus. The newly described species are illustrated with photographs of the adults and the genitalia.